Filosofia no ensino médio: promovendo o pensamento crítico e a cidadania ativa dos estudantes - Rodrigues, Benedito de Paula (Universidade Federal de São Carlos, 2026)
This dissertation examines the inclusion of philosophy in the high school curriculum as an instrument for promoting critical thinking and active citizenship. The study problematizes the historically unstable trajectory of the subject within Brazilian basic education and the impacts of the National Common Curricular Base (Base Nacional Comum Curricular – BNCC) and Law No. 13,415/2017 on its curricular status. Drawing on John Dewey as the central theoretical framework, the research also engages with Paulo Freire, Matthew Lipman, Karl Jaspers, and Theodor W. Adorno. The investigation adopts a qualitative approach, combining a literature review with fieldwork through a semi-structured questionnaire administered to 14 philosophy teachers from the São Paulo state public school system, in schools under the jurisdiction of the Regional Education Board (Diretoria de Ensino) of São José do Rio Preto. The findings reveal a central paradox: while philosophy faces a progressive institutionalization of its irrelevance – expressed in the reduction of instructional hours, the platformization of teaching, and the social perception of the subject as lacking practical utility – it elicits genuine student engagement when mediated through dialogic practices. The predominant strategy adopted by teachers is contextualization grounded in students' prior knowledge and everyday culture, supported by a methodological triad of oral discussion, text reading, and audiovisual resources. The primary difficulty identified is the incompatibility between the breadth of the curriculum and the available instructional hours, which gives rise to a documented practice of curricular disobedience: teachers select and reshape content to preserve the reflective quality of instruction. Skepticism regarding the subject's actual impact constitutes a significant finding, with teachers asserting that fostering critical consciousness is "very difficult and rare" given the weight of influences external to the school. Also noted is the perception of philosophy as a threat within the context of religious and political polarization. Conversely, the data confirms its function as a tool for critical discernment in the face of misinformation. Based on the findings, the research proposes recommendations that include thematic prioritization over extensive coverage of the philosophical tradition, the strengthening of dialogic spaces, and the positioning of the philosophy classroom as a laboratory for critical thinking. The study concludes that the effectiveness of philosophy teaching depends on a teaching praxis that articulates intellectual rigor with reflective experience, responding to the formative urgencies of a democracy in constant challenge.
Philosophy in high school: promoting critical thinking and active citizenship among students
Keywords: Emancipação; Escola pública; Filosofia; Emancipation; Public school; Philosophy; CIENCIAS HUMANAS::FILOSOFIA; 4. Educação de Qualidade